Assessment of Hypoxic Tissue Fraction and Prediction of Survival in Cervical Carcinoma by Dynamic Contrast-Enhanced MRI - Gaustad, Jon-Vidar; Rofstad, Einar K. (Frontiers in Oncology, 2021)
Tumor hypoxia is a major cause of treatment resistance and poor survival in locally-advanced cervical carcinoma (LACC). It has been suggested that Ktrans and ve maps derived by dynamic contrast-enhanced magnetic resonance imaging can provide information on the oxygen supply and oxygen consumption of tumors, but it is not clear whether and how these maps can be combined to identify tumor hypoxia. The aim of the current study was to find the optimal strategy for calculating hypoxic fraction and predicting survival from Ktrans and ve maps in cervical carcinoma. Ktrans and ve maps of 98 tumors of four patient-derived xenograft models of cervical carcinoma as well as 80 patients with LACC were investigated. Hypoxic fraction calculated by using Ktrans maps correlated strongly (P < 0.0001) to hypoxic fraction assessed with immunohistochemistry using pimonidazole as a hypoxia marker and was associated with disease-free and overall survival in LACC patients. Maps of ve did not provide information on hypoxic fraction and patient outcome, and combinations of Ktrans and ve were not superior to Ktrans alone for calculating hypoxic fraction. These observations imply that Ktrans maps reflect oxygen supply and may be used to identify hypoxia and predict outcome in cervical carcinoma, whereas ve is a poor parameter of oxygen consumption and does not provide information on tumor oxygenation status.